Manajemen Perpustakaan Sekolah Dasar Negeri 2 Rejang Lebong - Murniyanto Murniyanto (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to analyze how the implementation of library management in SD Negeri No. 2 Rejang Lebong Regency. Data analysis techniques used are interviews, observation and documentation. To analyze the data that has been obtained, the researchers analyzed qualitative data. The results showed that it was very visible that the students in terms of library administration organizing SDN No. 2 Curup has been implemented but is not ideal, there are still many shortcomings, both in terms of structure and foundations, the library office as far as the administration for library administration is very large, the variety of reading material centers according to the educational program concerned, not adequate and other supporting reference books, implying that the library of SDN No. 2 Curup cannot be expected to progress like the library used by various existing schools, on the grounds that the library of SDN No. 2 Curup is still inadequate with regards to assistance that encourages the best library, both in terms of administration and office other supporters. Therefore, the nature of the library must be improved again with the hope that this library can be utilized and utilized as well as possible by Curup Elementary School students.